2020
DOI: 10.1039/d0nj02134b
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent sensor based on oyster mushroom-carbon dots for sensing nitroarenes in aqueous solutions

Abstract: The synthesis of OM-CDs and their sensing application for NAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Raman spectrum was also measured to underline structural properties of the CDs and it is given in Figure 2. The two clear peak at 1344 and 1538 cm -1 in the spectrum is shown that is attributed to D-band (sp 3 defects) and G-band (sp 2 clusters) respectively [21,22]. The UV-Vis spectrum of turnip juice derived carbon dots is demonstrated in Figure 3.…”
Section: Resultsmentioning
confidence: 93%
“…Raman spectrum was also measured to underline structural properties of the CDs and it is given in Figure 2. The two clear peak at 1344 and 1538 cm -1 in the spectrum is shown that is attributed to D-band (sp 3 defects) and G-band (sp 2 clusters) respectively [21,22]. The UV-Vis spectrum of turnip juice derived carbon dots is demonstrated in Figure 3.…”
Section: Resultsmentioning
confidence: 93%
“…Further, they observed an increase in antibacterial activity with increased CDs concentration, and they reported anti-cancer activity with a half-maximal inhibitory concentration (IC 50 ) of 3.34 g mL −1 . In addition to this, Zulfajri et al [121] developed CDs using oyster mushroom (OM) for sensing nitroarenes (NAs). The study demonstrated that the sensing mechanisms such as fluorescence resonance energy transfer (FRET), inner filter effect (IFE) and photo-induced electron transfer (PET) quenched the fluorescence emission intensity of OM-CDs by NAs.…”
Section: Edible Mushrooms Derived Carbon Dotsmentioning
confidence: 99%
“…Because their outstanding characteristics, CDs have been widely utilized in biological sensors [15], chemical sensors [16], bioimaging agents [17], optoelectronic devices [18], electrocatalysts [19], energy devices [20], light-emitting devices [21], drug carriers [22], and cancer theragnostic devices [23]. Various carbon precursors have been utilized to produce CDs, including oyster and straw mushrooms [24][25][26], kumquat [27], kiwi fruit peel [28], turmeric leaf [29], glucose [30], phthalocyanine [31], and p-phenylenediamine [32].…”
Section: Introductionmentioning
confidence: 99%